25.3k views
5 votes
-4x+9y=9
x-3y=-6

solve. systems of equations

User Tnilsson
by
5.5k points

2 Answers

5 votes

Answer:

-3x + 6y = 3

Explanation:

-4x + x = -3x

9y - 3y = 6y

9 - 6 = 3

User Theanilpaudel
by
5.4k points
6 votes

9514 1404 393

Answer:

(x, y) = (9, 5)

Explanation:

My preferred method is to solve a system using a graphing calculator. That result is attached.

__

Here, you can multiply the second equation by 4 and add the first equation.

4(x -3y) +(-4x +9y) = 4(-6) +(9)

-3y = -15 . . . . . . . . . . simplify

y = 5 . . . . . . . . . . . . divide by -3

x -3(5) = -6

x = -6 +15 = 9

The solution is (x, y) = (9, 5).

-4x+9y=9 x-3y=-6 solve. systems of equations-example-1
User PeterT
by
4.7k points